2016
DOI: 10.4238/gmr.15017271
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 inhibitor alleviates spinal cord injury by decreasing apoptosis

Abstract: ABSTRACT. Spinal cord injury (SCI) is typically caused by trauma or disease, and it severely affects patients' motor function. The relationship between signal transducers and activators of transcription-1 (STAT1) and neuronal death after cerebral focal ischemia has been comprehensively studied, but its role in SCI remains largely unknown. This study investigated the protective effect of an STAT1 inhibitor on SCI. Thirty SD rats were SCIinduced and were then randomly divided into two groups (N = 15 each), eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In our study, in fact, we found that pSTAT1 was overexpressed in the neurons of R6/2 mice brain, as an effect of the lack of inhibition exerted by SHP-1 of which R6/2 mice neurons were devoid. Interestingly, STAT1 inhibition is able to reduce apoptotic cell death ( Wu et al, 2016 ). On the contrary, SHP-2 intensity of immunoreaction decreased with disease progression in R6/2.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, in fact, we found that pSTAT1 was overexpressed in the neurons of R6/2 mice brain, as an effect of the lack of inhibition exerted by SHP-1 of which R6/2 mice neurons were devoid. Interestingly, STAT1 inhibition is able to reduce apoptotic cell death ( Wu et al, 2016 ). On the contrary, SHP-2 intensity of immunoreaction decreased with disease progression in R6/2.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al's results indicated that selective STAT1 inhibition can reduce the injury of nerve tissue and locomotor dysfunction by regulating the inflammatory response and possible apoptosis (39). Wu et al also believed that STAT1 inhibitors reduced SCI by reducing apoptosis (40).…”
Section: Discussionmentioning
confidence: 99%
“…In the last two years, many research studies, focusing on the identification of drugs potentially effective in SCI treatment, have been published [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ,…”
Section: Overview Of Current Pharmacological Approaches For the Trmentioning
confidence: 99%